Evaluasi Usability pada Aplikasi MyTelkomsel dengan Menggunakan Metode Usability Testing - Willy Arief Pramono; Hanifah Muslimah Az-Zahra; Retno Indah Rokhmawati (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Telkomsel is one of the operator cellular providers. Telkomsel having a far vision fore and mission provide the best for community and nation. The only alternative form of Telkomsel is grow, develop, and successful. My Telkomsel application providing facilities to consumers to access the features such as costumers' data usage, pulse amount and data plan/data packet/packet of data for customer number, manage the name, email account, and social media connection, do in refilled pulse even bought data packets. My Telkomsel application in Google Play Store currently (23/8/2018) get 4.1 rating of the scale of 5 and has been reviewed by 600 thousand more users. However, around 60 thousand users give the rating of 1 that means My Telkomsel application assessed by some users is insufficient. Because of that, the measurement using the usability test is needed. The result of the test shows that usability level of criteria learnability is 1,12 faster. Criteria memorability based on total click and easy way to remember from 23 and 17,23 become 22 and 16,33, criteria efficiency is 95,97% means quite high, rate of criteria error gets 1,31% rate that means very low, and score of criteria satisfaction is 69 from SUS questioner, which means high enough.